Methods of consensus building for community based fisheries management in Bangladesh and the Mekong Delta - Sultana, Parvin; Thompson, Paul (International Food Policy Research Institute, 2003)
A method of consensus building for management of wetlands and fisheries using a systematic approach to participatory planning and initially developed in Bangladesh is now being applied in both Bangladesh and the Mekong delta. The method recognizes diversity in livelihoods and works through a structured learning and planning process that focuses on common interests. It works with each category of stakeholder separately to prioritize the natural resource problems that their livelihoods are largely dependent on, they then share and agree common priorities in plenary. Then the stakeholder groups separately analyze possible solutions and their impacts, before meeting in plenary to share their analysis and form a consensus on win-win solutions. The process identifies the collective actions that are needed to arrive at preferred solutions, and determines potential impacts on different stakeholders and responsibilities for implementation, monitoring and evaluation. We outline the process in the context of building social capital through consensus, and compare indicators of social capital as an outcome of its application in a Vietnamese village in the Mekong delta with the outcomes of a similar process in a floodplain wetland in Bangladesh.